Abnormally activated OPN/integrin αVβ3/FAK signalling is responsible for EGFR-TKI resistance in EGFR mutant non-small-cell lung cancer - Yulong Fu; Yang Zhang; Zhe Lei; Ting Liu; Tingting Cai; Anqi Wang; Wenwen Du; Yuanyuan Zeng; Jianjie Zhu; Zeyi Liu; Jian-an Huang (Journal of Hematology & Oncology, 2020)
Abstract Background Acquired epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) resistance limits the long-term clinical efficacy of tyrosine kinase-targeting drugs. Although most of the mechanisms of acquired EGFR-TKI resistance have been revealed, the mechanism of ~ 15% of cases has not yet been elucidated. Methods Cell viability was analysed using the Cell Counting Kit-8 (CCK-8) assay. Proteome profiler array analysis was performed to find proteins contributing to acquired EGFR-TKI resistance. Secreted OPN was detected by ELISA. Immunohistochemical analysis was conducted to detect expression of integrin αV in NSCLC tissue. The effect of VS-6063 on apoptosis and proliferation of PC9 gefitinib-resistant cells was detected by fluorescence-activated cell sorting (FACS) and clonogenic assays. A mouse xenograft model was used to assess the effect of VS-6063 on the sensitivity of PC9 gefitinib-resistant cells to gefitinib. Results OPN was overexpressed in acquired EGFR-TKI-resistant NSCLCs. Secreted OPN contributed to acquired EGFR-TKI resistance by activating the integrin αVβ3/FAK pathway. Inhibition of FAK signalling increased sensitivity to EGFR-TKIs in PC9 gefitinib-resistant cells both in vitro and in vivo. Conclusions OPN contributes to acquired EGFR-TKI resistance by up-regulating expression of integrin αVβ3, which activates the downstream FAK/AKT and ERK signalling pathways to promote cell proliferation in NSCLC.